2017
DOI: 10.1259/bjr.20170143
|View full text |Cite
|
Sign up to set email alerts
|

No differences in radiological changes after 3D conformal vs VMAT-based stereotactic radiotherapy for early stage non-small cell lung cancer

Abstract: Results of the present study indicate that the pattern of radiological lung changes following SBRT for peripheral early stage non-small-cell lung cancer is not influenced by the different techniques used for planning and delivery. Advances in knowledge: This comparative observational study shows that smaller margins, image guidance and most importantly dose distribution do not change the pattern of radiological injury after lung SBRT; the same scoring system can be used, and expected incidence is similar.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…A Dutch series aiming to compare clinical and radiographic rates of pneumonitis between 3DCRT and VMAT did not uncover differences in early follow-up 19. A similar analysis focused on radiographic changes following SBRT of either 3DCRT or VMAT likewise was not able to appreciate a difference after a median follow up of 20.5 months 20…”
Section: Discussionmentioning
confidence: 92%
“…A Dutch series aiming to compare clinical and radiographic rates of pneumonitis between 3DCRT and VMAT did not uncover differences in early follow-up 19. A similar analysis focused on radiographic changes following SBRT of either 3DCRT or VMAT likewise was not able to appreciate a difference after a median follow up of 20.5 months 20…”
Section: Discussionmentioning
confidence: 92%
“…Previous reports showed that the V 5 of the lungs is unlikely to affect the grade of radiation pneumonitis. [ 39 40 ] V 20 is a more well-known risk factor for symptomatic radiation pneumonitis than V 5 . [ 41 ] The KBPs generated lower V 20 than the CLPs in both the closed- and open-loop validations, although there was no significant difference.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to radiological changes after lung SBRT, Badellino et al reported that late changes occurred in approximately 60% of patients treated with 3D-CRT and VMAT without differences between the two techniques in radiological patterns. 8 To date, there is little information on the functions of these high-dose regions inside and outside the PTV as a normal lung after tumor control in patients without late fibrotic changes and the contributions of these regions to RP risk. However, our findings showing increasing differences between the 3D-CRT and IMRT plans in high-dose parameters, including the V48 and V50, according to increasing PTV need to be considered in relation to the potential clinical significance of the high-dose region and tumor characteristics in lung SBRT.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6] Furthermore, some studies have recently compared the differences in radiological changes after lung SBRT using two different techniques with differences in dose distributions. 7,8 Regarding toxic effects of lung SBRT, radiation pneumonitis (RP) is one of the most commonly studied toxic effects, with reported symptomatic RP rates ranging from 9% to 28%. 9 Together with clinical risk factors for RP, dosimetric factors, such as the mean lung dose (MLD) and the percentage of total lung volume receiving a specific dose, have been used to guide the dose limit in RT planning for lung cancer to prevent RP.…”
Section: Introductionmentioning
confidence: 99%